2020
DOI: 10.5534/wjmh.190009
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Gut Microbiota

Abstract: Humans carry numerous symbiotic microorganisms in their body, most of which are present in the gut. Although recent technological advances have produced extensive research data on gut microbiota, there are various confounding factors (e.g., diet, race, medications) to consider. Sex is one of the important variables affecting the gut microbiota, but the association has not yet been sufficiently investigated. Although the results are inconsistent, several animal and human studies have shown sex differences in gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
319
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(339 citation statements)
references
References 75 publications
(149 reference statements)
16
319
1
3
Order By: Relevance
“…Sex hormones, in particular androgens, seem critical in shaping the gut microbiota composition. In mice, sex differences in gut microbiota appear with the onset of puberty and upon castration: the gut microbiota of a castrated male resembles that of a female [33]. Likewise, transfer of gut microbiota from males to females increases female testosterone levels and protects from autoimmunity [34], while the absence of gut microbiota diminishes sex-specific gene expression and metabolism [30,31,35].…”
Section: Sex Differences In the Immune System And Immune Reactionsmentioning
confidence: 99%
“…Sex hormones, in particular androgens, seem critical in shaping the gut microbiota composition. In mice, sex differences in gut microbiota appear with the onset of puberty and upon castration: the gut microbiota of a castrated male resembles that of a female [33]. Likewise, transfer of gut microbiota from males to females increases female testosterone levels and protects from autoimmunity [34], while the absence of gut microbiota diminishes sex-specific gene expression and metabolism [30,31,35].…”
Section: Sex Differences In the Immune System And Immune Reactionsmentioning
confidence: 99%
“…32 Some studies have reported that women are more susceptible to the effects of cigarette smoke than men, 33,34 consistent with a more heightened innate immune response than in men. In addition, there are sex differences in microbiome diversity, 35 with women showing greater diversity. 36,37 Microbiome diversity has been linked to disinfectant use.…”
Section: Discussionmentioning
confidence: 99%
“…RESULTS: Children in homes with a higher frequency of use of cleaning products in infancy, as determined by an interquartile range increase, had higher odds of recurrent wheeze (adjusted odds ratio [OR] 1.35, 95% confidence interval [CI] 1.11-1.64), recurrent wheeze with atopy (adjusted OR 1.49, 95% CI 1.02-2.16) and asthma diagnosis (adjusted OR 1.37, 95% CI 1.09-1.70), but no increase in the odds of atopy at age 3 years (adjusted OR 1.14, 95% CI 0.96-1. 35). Compared with the lowest tertile of FUS exposure, infants in the highest tertile had higher odds of acquiring asthma.…”
mentioning
confidence: 99%
“…Men and women are known to exhibit gender-specific differences in their immune system and their gut microbiota composition (Kim et al 2020). Previously, the gut microbiota from males or females were transferred to germ-free animals of either the same or the opposing gender and, in fact, microbiota-independent gender differences in distinct immune cell repertoires were already present in germ free mice.…”
Section: Sniffing ɵMe (S)-cupmentioning
confidence: 99%